Is Ultrasonography an Effective Method for Diagnosing Degenerative Changes in the Temporomandibular Joint? - Barbara Wojciechowska; Arkadiusz Szarmach; Adam Michcik; Maciej Sikora; Barbara Drogoszewska (Biomedicines)
Background: The accurate diagnosis of degenerative joint diseases (DJDs) of the temporomandibular joint (TMJ) presents a significant clinical challenge due to their progressive nature and the complexity of associated structural changes. These conditions, characterized by cartilage degradation, subchondral bone remodeling, and eventual joint dysfunction, necessitate reliable and efficient imaging techniques for early detection and effective management. Cone-beam computed tomography (CBCT) is widely regarded as the gold standard for evaluating osseous changes in the TMJ, offering detailed visualization of bony structures. However, ultrasonography (US) has emerged as a promising alternative, offering a non-invasive and radiation-free option for assessing TMJ disorders. This study aims to evaluate the diagnostic accuracy of US in identifying degenerative changes in the TMJ, with CBCT serving as the definitive diagnostic reference. By analyzing the sensitivity, specificity, and predictive values of US in detecting key degenerative markers—such as subchondral erosion, osteophytes, and joint space narrowing—this investigation seeks to assess its utility as a screening tool and its potential integration into clinical workflows. Methods: Forty adult patients presenting temporomandibular joint disorders were included in our cross-sectional study. Each patient underwent a clinical examination and was subjected to cone-beam computed tomography (CBCT) and ultrasonography (US). A statistical analysis was performed to compare the imaging results from CBCT and US. Results: The results are summarized in three tables. The first table presents a comparative analysis of radiological outcomes in patients with temporomandibular joint disorders using different imaging techniques. CBCT demonstrated higher sensitivity in detecting osteophytes in the right mandibular head (27.50% vs. 7.50%, p = 0.027) and higher detection rates for erosions, though without a significant advantage over US. The second table analyzes the consistency of diagnostic results between CBCT and US. A moderate agreement was observed for detecting normal bone structures, with AC1 values of 0.58 for the right and 0.68 for the left mandibular head (p < 0.001). The third table evaluates the diagnostic accuracy of US compared to CBCT. US demonstrated a positive predictive value (PPV) of 90% for detecting normal conditions, indicating its high reliability as a screening tool for normal findings. US demonstrates higher effectiveness in ruling out certain issues due to its high specificity and negative predictive value. However, its lower sensitivity in detecting abnormalities may lead to both false-positive and false-negative results. Conclusions: US holds significant promise as a screening modality for detecting normal anatomical features of the temporomandibular joint, its limitations in identifying more complex degenerative changes necessitate a cautious and integrated approach to TMJ diagnostics.